Ependymoma and Carcinoid Tumor Associated with Ovarian Mature Cystic Teratoma in a Patient with Multiple Endocrine Neoplasia I. (10th April 2014) - Spaulding, Reed; Alatassi, Houda; Stewart Metzinger, Daniel; Moghadamfalahi, Mana
Abstract : Ovarian teratomas rarely undergo new neoplastic transformation and account for a small percentage of malignant ovarian germ cell neoplasms. Here we report a case of a 51-year-old woman with multiple endocrine neoplasia type I (MEN I) who was found to have an ependymoma and neuroendocrine tumor (trabecular carcinoid) associated with mature cystic teratoma of her left ovary. The ependymoma component displayed cells with round nuclei and occasional small nucleoli which were focally arranged in perivascular pseudorosettes and true rosettes. Rare mitoses were identified. No necrosis was present. Immunohistochemical staining was positive for S-100 and GFAP. The Ki67 proliferation index was very low (2-3%). In contrast, the endocrine tumor component was composed of small uniform cells with eosinophilic cytoplasm, round nuclei, and speckled chromatin. Immunohistochemical staining was positive for synaptophysin and focally positive for chromogranin. This rare case illustrates that MEN I may have an influence on the pathogenesis of ovarian teratomas as they undergo malignant transformation.